Fungicidas no controle da ferrugem asiática e sua influência na qualidade de sementes de soja - Olsen, Danielli (2012)
The chemical control is the main strategy for controlling the soybean asian rust. Thus, information about the efficiency of fungicides as well as the residual effect on seeds are needed to guide its correct use in the field. The aim of this work was to evaluate the efficiency of different active ingredients to control the asian rust, as well as their influence on the physiological and sanitary quality of soybean seeds. The experiment was conducted in Mafra, SC, in the 2010/2011 growing season, using the cultivars Syngenta 3358 RR and Nidera 6411 RR. The experimental design was randomized blocks with four replications of 14 treatments for the Syngenta cultivar and 15 treatments for the Nidera cultivar. The evaluated active ingredients were: tebuconazole (0,5 L p.c. ha-1), cyproconazole (0,3 L p.c. ha-1), azoxystrobin + cyproconazole (0,3 L p.c. ha-1) + Nimbus 0,5%v/v, pyraclostrobin + epoxiconazole (0,5 L p.c. ha-1) + Assist 0,5 L.ha-1, trifloxystrobin + tebuconazole (0,5 L p.c. ha-1) + Aureate 0,5 L.ha-1, picoxystrobin + cyproconazole (0,3 L p.c. ha-1) + Nimbus 0,45 L.ha-1, trifloxystrobin + cyproconazole (0,15 L p.c. ha-1) + Aureate 0,5 L.ha-1, azoxystrobin + tetraconazole (0,5 L p.c. ha-1) + Nimbus 0,5 L.ha-1, trifloxystrobin + prothioconazole (0,4 L p.c. ha-1) + Aureate 0,4 L.ha-1, pyraclostrobin + metconazole (0,5 L p.c. ha-1) + Assist 0,5 L.ha-1, pyraclostrobin + epoxiconazole (0,6 L p.c. ha-1) + Lanzar 0,3%v/v, azoxystrobin (0,35 L p.c. ha-1) + Assist 0,5%v/v, azoxystrobin + tebuconazole (0,5 L p.c. ha-1) + Assist 0,5%v/v, oxicarboxim (1,2 L p.c. ha-1) + Silwett 0,05%. The fungicides were applied at flowering (R2 stage) and at the beginning of the grain formation (R5.2 stage). It was evaluated: rust severity at seven and 14 days after the second fungicide application; yield (kg ha-1), thousand seed weight (g), germination (%), electrical conductivity (µS.cm-1.g-1), accelerated aging (%), and seed health, through the Blotter Test. The results indicate that the triazole fungicides combined with strobilurins are more effective in controlling the asian rust. Fungicides do not affect in the physiological and sanitary quality of seeds of both cultivars.